Correlation Of Classroom Management On Learning Motivation In SDN 156 Sub-District Kalaena Luwu Timur - Ardiansyah, Ardiansyah; Achmad, Widya Karmilasari; AP, Nurfaizah (International Journal of Elementary School Teacher, 2021)
This research examines the following problems: (1) How is the description of the classroom management of SDN 156 students in Kalaena District, East Luwu Regency? How is the learning motivation of SDN 156 students in Kalaena District, East Luwu Regency? (3) Is there a relationship between classroom management and student motivation at SDN 156, Kalaena District, East Luwu Regency? The purpose of this study was to determine: (1) To determine the description of the classroom management of SDN 156 students, Kalaena District, East Luwu Regency; (2) To determine the learning motivation of students of SDN 156, Kalaena District, East Luwu Regency; (3) To find out whether there is a relationship between classroom management and student motivation at SDN 156, Kalaena District, East Luwu Regency. This research approach is quantitative with the type of ex-postfacto research. This research design is correlational. The sample selection in this study using purposive sampling technique. The data collection techniques used were questionnaires and documentation. The normality test used the KolmogrovSmirnov Normality Test with the results of a questionnaire that was normally distributed. Hypothesis testing uses 2 methods, namely the correlation test and the coefficient of determination test. An overview of the class management of SDN 156 students in Kalaena district, East Luwu district, is in the Hight category. As for the description of student learning motivation when it is in the sufficient category too. The conclusion of the study shows that there is a positive and significant relationship between classroom management and student motivation in SDN 156, Kalaena District, East Luwu Regency.